Development Of Electrochemical Biosensor Based On Nylon-6 Membrane - Shaimi, Roswani (2019)
Millions of people die due to the unavailability and inaccessible of diagnostics facilities especially in controlling crucial diseases, which led to the progressive development of biosensor. Unfortunately, direct oxidation of target analyte at the bare electrode of a biosensor is an irreversible process and requires a high overpotential, resulted in electrode fouling and low sensitivity. Nylon-6 membrane modified electrodes have been proposed to overcome this problem. As an immunoassay, the biochemical reaction between target and capture analyte takes place on the surface of the nylon-6 membrane, then translated to measurable resistance signal. The present study elucidates the morphology characteristic of nylon-6 as protein immobilization membrane and their influences in biological recognition interface. The nylon-6 membranes were synthesized via dry phase inversion with different concentration of nylon-6 polymer in a range of 16 wt. % to 28 wt.% and different types of additives (water and methanol) in dope solution. The developed nylon-6 membrane, N-16B, with 16 wt. % nylon-6 polymer and methanol as non-solvent had demonstrated the fastest lateral wicking speed (1.07 mm/sec) and excellent protein immobilization capacity (1,650.00 + 85.84 μg/cm3). The current study revealed the importance of membrane morphology that affects the sensitivity and effectiveness of an immuno-sensing device. The stability issue in biomolecule immobilization has been overcomed by integrating glutaraldehyde (GA) onto nylon-6 membrane prior to protein immobilization. The preliminary study was carried out to study the effect of incubation time, pH and concentration of GA on protein binding of the nylon-6 polymer. The optimum conditions of GA integration were found at 40 minutes of incubation time, pH 7.5 and 1 wt. % of GA concentration. Statistical analysis using crossed design programme was performed and the optimum GA integration conditions from the statistical analysis were found at 25 wt. % of the nylon-6 polymer, 75 wt. % of mixture solvent + nonsolvent, pH 9.0 and 70 minutes of incubation time. The experimental results showed that the GA as a cross-linker reagent at optimum conditions was able to achieve better GA attachment for latter protein immobilization. Further study has been explored on the preparation of conductive polyaniline-iron oxide (PANI/Fe2O3) that served as the electrical signal transducer, to convert the electrochemical interactions to a measurable resistance signal. PANI was synthesized via oxidative polymerization of aniline monomer (AM) in the presence of ammonium persulfate (APS). 0.2 M concentration of AM and 1:3 volume ratio of AM:APS were found to produce PANI logged with the highest ionic conductivity response at 7.565 + 0.262 mS/cm. The study had reviewed the interesting aspect of different state of PANI as one of the important conducting material for electronic/electrical devices. Subsequently, a membrane-based amperometric sensor was assembled and electrochemical activities ascorbic acid (AA, target analyte) and ascorbate oxidase (capture analyte) were evaluated. The detection limit of the sensor was found at 5.77 mM and the Michaelis–Menten constant (Km) was calculated as 26.76 mM. Electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV) and differential pulse voltammograms (DPV) responses were carried out to analyze the electrochemical double layer on the working electrode. The developed nylon-6 membrane has provided a promising detection platform for sensor construction and suitable for practical application in pharmaceutical or clinical analysis and agricultural crops.